PENERAPAN ALAT PERMAINAN EDUKATIF BOWLING ANGKA UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA DINI KELOMPOK A DI RA AL-BAROKAH BANGSALSARI JEMBER - Dewi Sukma Melati; Naily Inayatul Maghfirah (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study aims to determine the role of numbers bowling educational game tools on cognitive abilities in early childhood. Usually, early childhood has problems in improving their cognitive abilities, so unique and interesting ways are needed to improve children's cognitive abilities. This method can be done in the form of games, because games can cause pleasure and satisfaction for a child, namely through the game of number bowling. This research is a qualitative research with a type of field study research conducted by collecting various methods. The data collection technique in this study uses observation, interview, and documentation techniques. Meanwhile, the data analysis technique is through data reduction, presentation, and conclusion drawn. The results of the study show that through this number bowling educational game tool, children are able to develop their cognition by maximizing children's thinking patterns when they want to roll the ball, so that they can drop the number bowling pin that has been arranged by the teacher. Children can name the colors and numbers on the bowling numbers they drop.